Sposoby istnienia muzyki klasycznej w filmie fabularnym - Dobrochna Dabert (Przestrzenie Teorii)
The article deals with the topic of classical music in film. Classical music can in various ways semantically and aesthetically contribute to the film's message. It can enrich the film's message created at the level of words and images, create new and specific musical meanings but also modify or negate meanings created by words and images. The varied roles of classical music in film are explored on many examples of Polish and world cinematography.